Climatic variability and morbidity and mortality associated with particulate matter - Poliany Cristiny de Oliveira Rodrigues; Samya de Lara Pinheiro; Washington Junger; Eliane Ignotti; Sandra de Souza Hacon (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE The objective of this study has been to analyze whether fine particulate matter (PM2.5), as well as its synergistic effect with maximum temperature, humidity, and seasons, is associated with morbidity and mortality from cardiovascular diseases. METHODS This is an ecological study of time series. We have used as outcomes the daily death and hospitalization records of adults aged 45 years and over from 2009 to 2011 of the municipalities of Cuiabá and Várzea Grande, State of Mato Grosso, Brazil. We have used Poisson regression using generalized additive models, assuming a significance level of 5%. The model has been controlled for temporal trend, seasonality, average temperature, humidity, and season effects. Daily concentrations of PM2.5 (particulate material with aerodynamic diameter less than 2.5 micrometers) have been obtained by converting the values of optical aerosol thickness. Maximum temperature, humidity, and seasons have been separately included in the model as dummy variables for the analysis of the synergistic effect of PM2.5 with morbidity and mortality from cardiovascular disease. We have calculated the percentage increase of relative risk (%RR) of deaths and hospitalizations for the linear increase of 10 μg/m3 of PM2.5. RESULTS Between 2009 and 2011, the increase in PM2.5 was associated with a %RR 2.28 (95%CI 0.53-4.06) for hospitalizations on the same day of exposure and RR% 3.57 (95%CI 0.82-6.38) for deaths with a lag of three days. On hot days, %RR 4.90 (95%CI -0.61-9.38) was observed for deaths. No modification of the effect of PM2.5 was observed for maximum temperature in relation to hospitalizations. On days with low humidity, %RR was 5.35 (95%CI -0.20-11.22) for deaths and 2.71 (95%CI -0.39-5.92) for hospitalizations. In the dry season, %RR was 2.35 (95%CI 0.59-4.15) for hospitalizations and 3.43 (95%CI 0.58-6.35) for deaths. CONCLUSIONS The PM2.5 is associated with morbidity and mortality from cardiovascular diseases and its effects may be potentiated by heat and low humidity and during the dry season.